Feedlot performance, health, and carcass characteristics of beef heifers treated with Cydectin® or Dectomax® at processing - R.L. Hale; D. Gray; R. Armendariz (Kansas Agricultural Experiment Station Research Reports, 2005)
Two parasite-control products were compared in an experiment evaluating growth performance, health, and carcass characteristics. Crossbred heifers (n=1747; 837 lb average weight) were randomly assigned to receive either Cydectin® or Dectomax®. Both products were administered at processing at 1 ml per 22 lb of body weight. Cattle were randomly allotted to 12 paired pens by treatment based on source, truckload, and arrival date. Fecal egg counts taken at processing (9.74 eggs per gram) and at reimplanting (0 eggs per gram) indicated that both products were effective in eliminating adult female gastrointestinal parasites. No differences were detected in average daily gain, feed intake, feed efficiency, or most carcass characteristics. Respiratory pulls, realizer cattle, and death loss did not differ between treatments. In this experiment, similar growth performance, health, and carcass traits were observed for heifers treated with either macrocyclic lactone product.
Keywords: Cattlemen' s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Cydectin®; Dectomax®